The SLRS synchronous imperative programming language (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2000)
This paper describes the synchronous imperative programming language SLRS. After a brief overview of the language we define its behavioural semantics.